Metales biodisponibles en la cuenca alta del río Torres-Vizcarra, departamentos de Ancash y Huánuco - Chira Fernández, Jorge (2010)
Application of sequential extraction technique allows us to define the fractions of the metallic elements that move in a given environment, identifying bioavailable fractions and thus the actual environmental impact of the dispersion of heavy metals in sediments. The total analysis results compared to the recommended levels the Andalusian show that arsenic and zinc exceeded the so-called action thresholds, assuming that the soil is contaminated at levels high toxicity. The results of chemical speciation indicates that fractions of metals are primarily associated with the hydrated oxides of iron and manganese and the organic material and the residual fraction, so that the bioavailable fraction reaches fairly low levels, meaning that no there is a negative impact on the life cycle in the upper reaches of rivers Vizcarra Torres.